Optimal Weights for Marital Sorting Measures - Frederik Almar; Bastian Schulz (Institute of Labor Economics (IZA), 2023)
Changing distributions of male and female types affect the measurement of educationbased marriage market sorting. We develop a weighting strategy that minimizes the distortion of sorting measures due to changing type distributions. The optimal weights reflect that female type distributions have changed relatively more in recent decades. Based on our weighted measure, we document increasing sorting in Denmark between 1980 and 2018. Alternative measures suggest flat or decreasing trends.
Keywords: C43; D10; J11; J12; 330; positive assortative mating; marriage market sorting; homophily; educational attainment; sorting measures; aggregation